Movies as an authentic input in L2 speaking class: A Dynamic Usage-Based approach in EFL teaching in Indonesia - Hoinbala, Festif Rudolf (International Journal of Language Education, 2022)
One of the characteristics of a Dynamic Usage-Based (DUB) approach to the second language is schematic patterns emerge through use and interaction where the intense focus is in input. Video or movie as an example of authentic input often provides a natural context for conversations to emerge among the students and teacher in class since students want to know or share their opinions about the characters or events in the movie. This recent study's objective was to demonstrate that movies or videos provide an authentic input in L2 class. This study's population sample was 30 students of the second-year English Education program in 2021 at Artha Wacana Christian University Kupang in Indonesia. A simple random sampling technique was applied to select this sample. The study was conducted over 12 teaching periods using the DUB approach, where the procedure was processed by a pre-test, treatment, and ended by post-test. The instruments used in this study were speaking class lesson plans and English speaking tests (both pre-test and post-test). The Mean and Paired Sample T-Test was employed in the data analysis. The result shows a significant difference between students' English speaking competence taught using movies and those taught using a conventional method. Therefore, using movies in classroom teaching is in line with the DUB approach as one of its principles is authentic input.